Simple Methods and Rational Design for Enhancing Aptamer Sensitivity and Specificity - Kalra, Priya; Dhiman, Abhijeet; Cho, William C.; Bruno, John G.; Sharma, Tarun K. (Frontiers in Molecular Biosciences, 2018)
Aptamers are structured nucleic acid molecules that can bind to their target with high affinity and specificity. However, conventional SELEX (Systematic Evolution of Ligands by EXponential enrichment) methods may not necessarily produce aptamers of desired affinity and specificity. Thus to address the aforementioned limitation, this review is intended to suggest some useful approaches and tips along with novel selection methods to enhance evolution of aptamers of highest performance. This article covers latest novel innovations as well as broad range of well-established approaches one can follow to improve the individual binding parameters (aptamer affinity, avidity, specificity and/or selectivity) of aptamers during and/or post-SELEX. The advantages and limitations of aptamer individual selection methods and post-SELEX optimizations, along with rational approaches to overcome these limitations are elucidated in each case. Further the impact of chosen selection milieus, linker-systems, aptamer cocktails and detection modules utilized in conjunction with target-specific aptamers, on the overall assay performance are discussed in detail, each with its own advantages and limitations. The simple variations suggested are easily available for facile implementation during and/or post SELEX to develop ultrasensitive and specific assays. Finally, success stories of established aptamer-based assays are discussed, highlighting how they utilized some of the suggested methodologies to develop commercially successful point-of-care diagnostic assays.